2015
DOI: 10.1016/j.ydbio.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factors Ets1 and Sox10 interact during murine melanocyte development

Abstract: Melanocytes, the pigment-producing cells, arise from multipotent neural crest (NC) cells during embryogenesis. Many genes required for melanocyte development were identified using mouse pigmentation mutants. The variable spotting mouse pigmentation mutant arose spontaneously at the Jackson Laboratory. We identified a G-to-A nucleotide transition in exon 3 of the Ets1 gene in variable spotting, which results in a missense G102E mutation. Homozygous variable spotting mice exhibit sporadic white spotting. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Here, in agreement with Frith et al (2018), we found that posterior NCCs express ETS1, previously thought to be restricted to anterior NCCs, and promote chondrocyte differentiation (Sugiura and Ito, 2010). Moreover, ETS1 has been linked to trunk melanocytes (Gao et al, 2010;Saldana-Caboverde et al, 2015;Ye et al, 2010). NC culture conditions for differentiation reveal a wider potential for NCCs in vitro than in in vivo, and thus inductive signals in vitro appear stronger than those present in vivo (Abzhanov et al, 2003;Dupin et al, 2018;McGonnell and Graham, 2002).…”
Section: Differentiation Potential Of Posterior Ncsupporting
confidence: 82%
“…Here, in agreement with Frith et al (2018), we found that posterior NCCs express ETS1, previously thought to be restricted to anterior NCCs, and promote chondrocyte differentiation (Sugiura and Ito, 2010). Moreover, ETS1 has been linked to trunk melanocytes (Gao et al, 2010;Saldana-Caboverde et al, 2015;Ye et al, 2010). NC culture conditions for differentiation reveal a wider potential for NCCs in vitro than in in vivo, and thus inductive signals in vitro appear stronger than those present in vivo (Abzhanov et al, 2003;Dupin et al, 2018;McGonnell and Graham, 2002).…”
Section: Differentiation Potential Of Posterior Ncsupporting
confidence: 82%
“…These results for SOX10 in melanocytes correlate with previous data showing other SOX family members can bind to super-enhancers and regulate lineage-specific genes in chondrocytes and hair follicle stem cells [37,38]. Strikingly, the super-enhancer-associated genes bound by SOX10 included MITF, TFAP2A, ETS1, ZEB2, and SNAI2, each lineage-specific transcription factors known to play important roles in melanocyte development and pigmentation [41,66,67,[96][97][98][99][100]. Several of these factors exhibit co-binding and/or regulation of one another during neural crest and melanocyte development; for example, ETS1 and SOX10 interact to promote proper melanocyte development [40,99], TFAP2A and MITF interact to regulate pigmentation [54,100], and SOX10 activates MITF, while MITF has been suggested to have the capacity to both activate and repress SOX10 expression [74-77, 101, 102].…”
Section: Discussionsupporting
confidence: 86%
“…Strikingly, the super-enhancer-associated genes bound by SOX10 included MITF, TFAP2A, ETS1, ZEB2, and SNAI2, each lineage-specific transcription factors known to play important roles in melanocyte development and pigmentation [41,66,67,[96][97][98][99][100]. Several of these factors exhibit co-binding and/or regulation of one another during neural crest and melanocyte development; for example, ETS1 and SOX10 interact to promote proper melanocyte development [40,99], TFAP2A and MITF interact to regulate pigmentation [54,100], and SOX10 activates MITF, while MITF has been suggested to have the capacity to both activate and repress SOX10 expression [74-77, 101, 102]. SOX10 binding at super-enhancers near these genes suggests SOX10 is integral to the complex regulatory cross talk exhibited by these lineage-determining transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…We found that BET inhibition suppressed the expression of additional pigmentation genes regulating these melanocyte functions. The mRNA levels of many transcriptional regulators that affect the level of pigmentation, including Sox10 [58], Ets1 [59], and Irf4 [39], were also reduced while the expression of Tfap2 was strongly increased in both Melb-a melanoblasts and SK-MEL-147 melanoma cells. TFAP2, which promotes melanocyte differentiation by activating a subset of MITF target genes, is frequently lost in melanoma due to silencing by CpG methylation [60,61].…”
Section: Discussionmentioning
confidence: 99%